Relating human physiology content to COVID-19: a strategy to keep students in touch with physiology in times of social distance due to pandemic - Alves, Niege (Adv Physiol Educ, 2021)
In 2020 universities had to quickly implement remote education alternatives as a result of the social distancing due to the COVID-19 pandemic. To keep students engaged with the university, we implemented a teaching-learning model that relates physiology contents to the COVID-19 pandemic using online educational platforms. A 1-mo web course was proposed for health sciences students from the Federal University of Pampa. It included synchronous meetings twice a week and asynchronous activities using scientific articles, case studies, and interactive online tools. The students approved the methodology developed, assessing it as dynamic and innovative. They reported that the activity helped to better understand the relations between COVID-19 and physiological systems. The web course also contributed to the identification of reliable sources of news and stimulated the sharing of scientific content with their families. We concluded that the use of online platforms contextualizing the physiology content considering current events helps students in learning human physiology and improves their abilities to apply this information to their daily life, in this specific case, regarding the COVID-19 pandemic.